Comparative analysis of video-augmented and traditional training methods in developing interpreter skills across multilingual contexts - Almahasees, Zakaryia; Albudairi, Yousef (Research Journal in Advanced Humanities, 2025)
The research examines the impact of video-based training on improving interpreting skills compared to the traditional method. The research population consisted of 20 students enrolled in the Simultaneous and Consecutive Interpreting Course 1 at Applied Science Private University, divided into two groups: one undergoing video-based training and the other undergoing traditional training. The participants' interpreting competencies were measured using pretests and post-tests that quantified key competencies in accuracy, terminology use, fluency of delivery, and cultural competency. This study prioritized the importance of real-life interpreting contexts, such as medical, legal, conference, and community settings, in which video-enhanced instruction provided real-life, experiential learning opportunities. The findings indicated that the video-augmented training group showed significant improvements on all dimensions compared to the control group, which received conventional training. Even the survey remarks corroborated that video-augmented training was perceived to be more realistic, applicable, and interactive than traditional training. The findings confirm that video-augmented training is superior to conventional training in enhancing interpreting skills, as it creates a more realistic and engaging learning environment. The findings suggest that incorporating video-based teaching approaches into interpreting training curricula may effectively prepare students for real-life interpreting assignments.